104 Grazing Evaluation of Two Bermudagrass Bases Interseeded with Alfalfa for Stocker Production in Southeastern US. (8th March 2022) - Burt, Justin C; Silva, Liliane; Mullenix, Kim; Prevatt, Chris; Baxter, Lisa; Shay, Nicholas; Whatley, Kendall S; Doblado, Andrea M Osorio; Tucker, Jennifer J
Abstract: Alfalfa ( Medicago sativa ) has shown promise in the Southeastern United States when interseeded into bermudagrass ( Cynodon dactylon ) to reduce reliance on synthetic N fertilization while also providing a high-quality grazable forage. However, data is limited when grazing alfalfa interseeded into different bermudagrass bases with stockers in the Southeastern U.S. A two-year grazing evaluation was conducted in a randomized complete block design with two replications from June-October 2020 (Y1) and April-October 2021 (Y2) at the University of Georgia Tifton Campus Better Grazing Program in Tifton, GA, to compare stocker cattle performance when grazing 'Bulldog 805' alfalfa interseeded into either 'Russell' or 'Tifton-85' bermudagrass (RAG and TAG, respectively). Paddocks (1-ha) were split into 4 (0.25-ha) sections and rotationally grazed to 10 cm using the put-and-take stocking method with two tester steers for each treatment (Y1 BW=228.3±27.02 kg; Y2 BW=183.1±20.8 kg). Paddock sections were evaluated pre- and post-grazing for herbage availability, botanical composition, and nutritive value. Stocker steers were weighed at study initiation, conclusion, and on a 28d interval for calculation of ADG and gain/ha. Data were analyzed using the PROC MIXED procedure of SAS 9.4. Differences for herbage mass, gain/ha, and stocking density were not detected seasonally but were observed within grazing cycle with RAG being greater in the earlier season, TAG being greater in the later portion of the grazing season, and no difference during the grazing cycles that occurred in the hot summer months. This study suggests that the bermudagrass variety utilized in the alfalfa-bermudagrass mixture will influence stocking management decisions.